2020
DOI: 10.1177/1178633720970569
|View full text |Cite
|
Sign up to set email alerts
|

A Systemic Literature Review and Meta-Analysis Reporting the Prevalence and Impact of Methicillin-Resistant Staphylococcus aureus Infection in India

Abstract: Aim and objective: This systematic review and meta-analysis was conducted to assess the prevalence, burden and epidemiology of methicillin-resistant S. aureus (MRSA). This systemic review was also aimed to highlight the challenges in the diagnosis and management of methicillin-resistant S. aureus (MRSA) in India (for all age groups). We also examined the published literature on the available treatment options and the role of prevention in the management of MRSA in India. By summarizing the currently available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…Our study observed a positive association between MRSA infection and age [ 31 ], and a systematic literature review from India also showed similar evidence [ 32 ]. Older age groups are more prone to get infected due to decreased host resistance and increased exposure to healthcare settings.…”
Section: Discussionsupporting
confidence: 77%
“…Our study observed a positive association between MRSA infection and age [ 31 ], and a systematic literature review from India also showed similar evidence [ 32 ]. Older age groups are more prone to get infected due to decreased host resistance and increased exposure to healthcare settings.…”
Section: Discussionsupporting
confidence: 77%
“…The finding of our study was consistent with other previous findings in Nepal [ 30 – 33 ]. However, the prevalence varies in the different parts of Nepal [ 34 , 35 ] and India [ 36 ]. This finding can show the use of beta-lactam antibiotics against Gram-positive organisms in hospital and community settings.…”
Section: Discussionmentioning
confidence: 99%
“…aureus, a facultative intracellular pathogen, is a common pathogen responsible for both community-and hospital-acquired infections [14]. As reported in Ghia et al's meta-analysis, the treatment options identified for MRSA in India include arbekacin sulfate, vancomycin hydrochloride, teicoplanin, daptomycin, and oritavancin [15]. However, many anti-staphylococcal drugs' lack of intracellular activity could be responsible for persistent S. aureus infections such as persistent bacteremia and failure of therapy.…”
Section: Discussionmentioning
confidence: 99%